2015
DOI: 10.4149/bll_2015_047
|View full text |Cite
|
Sign up to set email alerts
|

The histopathological effects of levosimendan on liver injury induced by myocardial ischemia and reperfusion

Abstract: Abstract:Background: The aim of this study was to evaluate the histological and immunohistochemical effects of levosimendan on liver injury induced by myocardial ischemia and reperfusion (I/R) in a rat model. Methods: Twenty-four male Wistar Albino rats were randomly divided into the four groups: Group C (Control, n = 6), Group I/R (n = 6), Group BI (I/R group treated with levosimendan before ischemia, n = 6), and Group AI (I/R group treated with levosimendan after ischemia, n = 6). Myocardial I/R was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Histopathological examination was performed as described previously to observe the pathological changes in the liver tissues and determine the extent of liver fibrosis [ 30 32 ]. Samples of liver tissue were fixed in 10% buffered formalin, routinely embedded in paraffin, cut into 4 mm thick sections, and stained with hematoxylin and eosin (HE) and Masson trichrome staining for examination by light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Histopathological examination was performed as described previously to observe the pathological changes in the liver tissues and determine the extent of liver fibrosis [ 30 32 ]. Samples of liver tissue were fixed in 10% buffered formalin, routinely embedded in paraffin, cut into 4 mm thick sections, and stained with hematoxylin and eosin (HE) and Masson trichrome staining for examination by light microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, they concluded that levosimendan significantly ameliorates damage in a liver IRI model, especially when given before induction of ischemia. [14] In our present study, the infusion of levosimendan was maintained during the reperfusion. In the levosimendan groups, both serum AST and ALT levels and histopathological injury score were significantly decreased.…”
Section: Discussionmentioning
confidence: 86%
“…In their experimental study, Oktar et al [14] used levosimendan in liver injury induced by myocardial ischemia and reperfu- sion. They used a cycle of 60 minutes of ischemia and 60 minutes of reperfusion for rat liver and used levosimendan at a dose of 100 mcg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a limited number of clinical and experimental studies on distal organ I-R-related liver injury. In literature, there two studies that have reported the histopathological and biochemical effects of distal organ ischemia reperfusion on liver [ 17 ] . Based on similar studies, we planned to use I-R duration as 60 minutes of ischemia and 120 minutes of reperfusion [ 14 , 16 ] .…”
Section: Discussionmentioning
confidence: 99%